230 Thorium Dating of Toolstone Procurement Strategies, Production Scale and Ritual Practices at The Mauna Kea Adze Quarry Complex, Hawai'i - McCoy, Patrick C.; Nees, Richard; Weisler, Marshall I.; Jian-Xin, Zhao (Waka Kuaka, 2013)
230 Thorium dates on unweathered pieces of branch coral from the Mauna Kea Adze Quarry Complex suggest that a significant part of this quarry, the largest in the Hawaiian Islands, was in use by the mid-14th to mid-15th centuries AD. The dates also point to the high probability of labor intensive mining of subsurface toolstone by this date, in addition to the much easier strategy of procuring toolstone from the surface. While there is abundant evidence that adze manufacture on Mauna Kea, like the making of a Hawaiian canoe, was an "affair of religion," branch coral was rarely used in the several different forms of ritualisation that have been documented in the quarry. Possible reasons for this are briefly explored in this short paper, which is one more contribution to refining the chronology of this highly significant and important archaeological complex.